The Social Media’s Effect on Student Consumption Behavior - Hafizh Fitrianna (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
This study aims to see how social media affects students' lifestyles. The focus of this research is assessing the consumptive behavior of students with the presence of social media. There are two money variables that will be tested in this article, the independent variable is social media and the dependent variable is student consumptive behavior. This article uses the Pearson correlation method to process correlation data or the relationship between social media and student consumptive behavior. Collecting data using a survey method, namely by distributing questionnaires to 81 respondents. The selected respondents are students. The respondent's questionnaire data was tested for validity to determine the validity of the questionnaire data. The questionnaire data was also tested for reliability to determine its consistency. All respondent data was processed using SPSS version 22. The results of the validity test of all questionnaire data were declared valid with the r arithmetic value higher than r table. The results of the reliability test of all questionnaire data were declared reliable with an alpha value greater than r table. The results of the correlation test for variable X against Variable Y using Pearson correlation. The result is that there is no significant effect between social media on the consumptive behavior of students.